1999
DOI: 10.2134/agronj1999.914690x
|View full text |Cite
|
Sign up to set email alerts
|

Early‐ and Late‐Season Grazing of Orchardgrass and Fescue Hayfields Overseeded with Red Clover

Abstract: for beef producers. However, Frame et al. (1998) state that a grass-legume sward with no added N can produce Low-cost alternatives to hay feeding for wintering the beef herd the same DM yield as a pure grass sward with 100 to (Bos taurus L.) are needed to design sustainable production systems 250 kg N ha Ϫ1 applied. Red clover is reported to be one for northern Appalachia. This study was conducted to compare forage of the easiest legumes to establish in renovated sods production, quality, and botanical compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 13 publications
4
25
1
Order By: Relevance
“…Mixed pastures can improve animal performance, especially when grasses are intercropped with clovers (Prigge et al 1999;Papadopoulos et al 2001). Alfalfa (Medicago sativa L.) also is known for its ability to increase both the yield and quality of pasture mixtures.…”
mentioning
confidence: 99%
“…Mixed pastures can improve animal performance, especially when grasses are intercropped with clovers (Prigge et al 1999;Papadopoulos et al 2001). Alfalfa (Medicago sativa L.) also is known for its ability to increase both the yield and quality of pasture mixtures.…”
mentioning
confidence: 99%
“…The growths were affected by decomposition processes connected with senescence (Marschner, 1995) and unfavourable weather conditions during winter. The great importance of winter weather conditions for yield and herbage quality was also described by Baker et al (1965), Balasko (1977), Prigge et al (1999), Wolf and Opitz von Boberfeld (2003), Wöhler (2003). Regarding the present results, the prevailing climatic conditions of the regions in Germany, Poland, Hungary and Czech Republic influenced DM decisively and were responsible DM (% of DM) Figure 2.…”
Section: Discussionmentioning
confidence: 81%
“…On the other hand, our results presented in this study show a significant difference not only between Festulolium and Dactylis glomerata but also between Festulolium and Arrhenatherum elatius. A CP content of about 100 g/kg DM is necessary to meet the demand of pregnant suckling cows Prigge et al (1999) observed digestibility in Dactylis glomerata lower than in Festuca arundinacea in winter. The higher silicon (Si) content in the forage of Dactylis glomerata reduced OMD.…”
Section: Discussionmentioning
confidence: 99%
“…The festucoid hybrids can be better adapted for use at the end of the growing season than the loloid hybrids (Opitz von Boberfeld and Banzhaf 2006). Besides the above-mentioned species, the use of Dactylis glomerata L. at the end of the growing season was shown by Prigge et al (1999). Holúbek et al (2007) found that the quality of Dactylis glomerata sharply decreased if the harvest date of the first cut was exceeded.…”
mentioning
confidence: 99%